Diálogos Sur-Sur y Sur-Norte, Freire y el colonialismo: la conexión necesaria - Fregoso Bailon, Raul Olmo (2024)
In this essay, we locate Freire within an understanding of colonialism and, thereby, read his work within necessary South-South and South-North critical dialogues. Paulo Freire’s Pedagogy of the Oppressed (2000 [1970]) is a foundational text, not only for critical pedagogy, but also for humanities in Latin America. Few would doubt that his work was influenced by Marxism and that it reflects and constitutes key currents within both Marxism writ large and Latin American Marxism specifically. Nevertheless, what could be interesting and what we focus on here is, not explaining the Marxist frameworks (again) in Freire’s work, but rather re-reading his work within his particular historical context, including an understanding of the confluences of colonialism, class, race, and servitude that persist in the present. Following Adriana Puiggrós continued re-reading and revitalizing of his contributions, we attempt to portray a general map of Freire’s connection with colonialism in Latin America to better leverage his thinking as part of emancipatory social movements and institutional interventions in the present. We emphasize leveraging Freire here because we find his work to be a necessary constituent in both South-South and South-North dialogues.